The Effect of garlic extract (Allium sativum) on the hatching rate of sea bass eggs (Lates calcarifer) - Afriani Sari; Ahmadi Bathlimus (BIO Web of Conferences)
The purpose of this study was to determine the effectiveness of giving garlic extract (Allium sativum) to the hatching rate of sea bass eggs (Lates calcarifer). This research was conducted in February-March 2024 at the Brackish Water Aquaculture Center Ujung Batee, Aceh Besar. The method used in this study was a completely randomized design (CRD) consisting of 5 treatments and 4 replicates. The concentration of garlic used includes treatment A which is 0 (control), treatment B 1.000 ppm, treatment C 1.500 ppm, treatment D 2.000 ppm, and treatment E 2.500 ppm. The results of this study showed the hatching rate (HR) of eggs ranged from 30.75-92.75% and the survival rate (SR) ranged from 20.75-89.25%. Based on the ANOVA test, the addition of garlic extract has a real significant effect (P<0.05) on the hatching rate of seabass eggs and the survival of sea bass larvae. Soaking eggs in garlic extract was found to be effective in inhibiting fungal attacks on sea bass eggs that had previously been infected with fungi. This is proven by the high percentage of egg hatching and survival rate of sea bass larvae. In this study, treatment D (2000 ppm) was the best treatment which produced a hatching rate percentage of 92.75%, with a survival rate 89.25%.